DAMPAK KETERBUKAAN PERDAGANGAN INTERNASIONAL, MODAL MANUSIA, DAN ALIRAN MODALTERHADAP PERTUMBUHAN EKONOMI NEGARA ASEAN-5, 1993-2013 - Widyawati, Retno Febriyastuti (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2017)
The globalization that takes place in the last few decades has led to international trade openness with regard to economic growth. The aim of this study is to examine the impact of international trade openness, the quality of human capital, and capital flows to the country's economic growth in ASEAN-5 in 1993-2013. The unit of analysis is the ASEAN-5 consists of: Indonesia, Malaysia, Philippines, Singapore, and Thailand. The method used is the typology of the State to determine the position of ASEAN-5 and Vector Error Correction Model (Vector Error Correction Model-VECM) to determine the impact of international trade openness, the quality of human capital, and capital flows as indicated by gross fixed capital formation (gross fixed capital formation) on economic growth. Results Quotients State is all ASEAN-5 changes position during the observation period 1993-2013 year. VECM results showed that the openness of international trade and the quality of human capital has a positive and significant correlation to economic growth in ASEAN-5 during the period 1993-2013. Gross fixed capital formation has a negative and significant impact on economic growth of ASEAN-5 countries during the period 1993-2013.